2020
DOI: 10.29047/01225383.261
|View full text |Cite
|
Sign up to set email alerts
|

Practical methodology for interwell tracer applications

Abstract: Tracer technology has been used in the oil industry to investigate the fluid flow behavior into the reservoir.  Using this technology is possible to obtain relevant data from the reservoir such as remaining oil accumulations, estimate volumetric sweep efficiency, define reservoir heterogeneities, identify flow channeling, and determine residual oil saturation (Sor).   This technology has been one of the most useful tools for reservoir characterization for several decades. The tracer is injected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…In order to understand the dynamic monitoring characteristics and heterogeneity characteristics of injection production wells in the monitoring area, judge the reservoir connectivity, and on this basis, systematically study the water breakthrough horizon, water breakthrough direction, and advancing speed of high water cut wells in the monitoring area, we should better understand the water drive law of injection production wells in the monitoring area and further describe the heterogeneity of well groups. Trace substance interwell nanometre tracer monitoring is carried out at the two horizons of Long 6 1 1 and Long 6 2 1 of well cluster 1 in the monitoring area. e fourthgeneration cross-well nanometre tracer monitoring technology is adopted in this monitoring.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to understand the dynamic monitoring characteristics and heterogeneity characteristics of injection production wells in the monitoring area, judge the reservoir connectivity, and on this basis, systematically study the water breakthrough horizon, water breakthrough direction, and advancing speed of high water cut wells in the monitoring area, we should better understand the water drive law of injection production wells in the monitoring area and further describe the heterogeneity of well groups. Trace substance interwell nanometre tracer monitoring is carried out at the two horizons of Long 6 1 1 and Long 6 2 1 of well cluster 1 in the monitoring area. e fourthgeneration cross-well nanometre tracer monitoring technology is adopted in this monitoring.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By analyzing the background natural quantities of 7 elements in the produced water of the oil well corresponding to the water injection well, it is found that the background concentrations of Yb and Er tracers are low. Yb and Er are preliminarily selected to inject tracers into well cluster J1, and output indication of tracers Yb and Er in long 6 1 1 and long 1) [12]. Based on the abovementioned data and the background concentration of the produced elements in the water injection well, it is finally determined that the tracers injected into well cluster J1 are Yb and Er, and layered injection is adopted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations